Deposition of Hydroxyapatite on Silica Made from Rice Husk Ash to Produce the Powder Component of Calcium Phosphate Cement - Tri Windarti; Widjijono Widjijono; Nuryono Nuryono (Indonesian Journal of Chemistry, 2021)
Hydroxyapatite (HA) has been deposited on silica (SiO2) particles to produce HA-SiO2 composite that will be used as the powder component of calcium phosphate cement. HA was expected to be on the composite surface to maintain its bioactivity. SiO2 was made by the sol-gel method, in which silicate solution was extracted from rice husk ash with NaOH solution. Deposition of HA on SiO2 was carried out by wet chemical deposition method at various Ca/Si molar ratio (in a range of 5–25) followed by calcination at 600 °C for 2 h. Results showed that HA was successfully deposited on SiO2 particles. The cell parameters of the HA crystals were slightly distorted by the presence of SiO2 and HA in the composite had a bigger cell volume than pure HA. The crystallite size of HA in the composites increased with the increase of the Ca/Si ratio but the values were smaller than pure HA. SiO2 acted as a morphology directing agent. At low Ca/Si ratio, the HA-SiO2 particles were in a form of short rod-like particles with sizes of < 50 nm, while at high Ca/Si ratio, a mixture of short and long rod-like particles with the size of < 100 nm was obtained. The zeta potential of composites was almost similar to pure HA. These properties indicated that HA-SiO2 composites support the bioactivity of injectable calcium phosphate cement.